2015
DOI: 10.1097/eja.0000000000000233
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and alveolar inflammatory response in the dependent and nondependent lung in patients undergoing lung resection surgery

Abstract: In lung resection surgery, the inflammatory response is similar in both lungs. However, the greater increase in TNF-α levels in the nondependent lung and the smaller increase of MMP-2 concentration in the dependent lung may increase the susceptibility to develop PPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 45 publications
1
13
1
1
Order By: Relevance
“…5,11,12,23,25 In all of these studies, the change in plasma levels of biomarkers was independent of intraoperative ventilation settings. The present study also shows distinct kinetics of TNF-α, IL-6, IL-8 between patients who do and do not develop PPCs, which is partly in accordance with what has been reported in other studies investigating patients undergoing lung resection, 22 oesophagectomy 18,19,21 or liver transplantation. 20 All three biomarkers had poor prognostic accuracy and cannot be used to predict PPCs with any reliability.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…5,11,12,23,25 In all of these studies, the change in plasma levels of biomarkers was independent of intraoperative ventilation settings. The present study also shows distinct kinetics of TNF-α, IL-6, IL-8 between patients who do and do not develop PPCs, which is partly in accordance with what has been reported in other studies investigating patients undergoing lung resection, 22 oesophagectomy 18,19,21 or liver transplantation. 20 All three biomarkers had poor prognostic accuracy and cannot be used to predict PPCs with any reliability.…”
Section: Discussionsupporting
confidence: 93%
“…5,17 Our data confirm results from previous investigations in patients undergoing abdominal surgery, 4,18,21 and cardiac or lung surgery. 5,17,22 However, the plasma levels of all three biomarkers were modest. Previous studies showed that plasma levels of biomarkers were not affected by surgery in patients with healthy lungs.…”
Section: Discussionmentioning
confidence: 96%
“…Unfortunately, this approach creates a "shunt-like" effect through the nondependent lung and results in hypoxemia [1]. Furthermore, OLV and surgical trauma are accompanied by the release of excessive amounts of inflammatory mediators and neutrophil elastase, which lead to pulmonary infection and systemic inflammatory response syndrome [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…4 Increased levels of pulmonary inflammatory markers in both the dependent and non-dependent lungs contribute to postoperative pulmonary complications after lung resection surgery. 5 Lung resection during VATS lobectomy could cause endothelial glycocalyx layer degradation, destruction of normal vascular permeability, and eventual acute lung injury (ALI) appearance. 6 Furthermore, one-lung ventilation (OLV), which has become necessary for improving surgical exposure with increased VATS use, can also contribute to ALI development.…”
Section: Introductionmentioning
confidence: 99%